2022
DOI: 10.1063/5.0097883
|View full text |Cite
|
Sign up to set email alerts
|

High-P–T impedance measurements using a laser-heated diamond anvil cell

Abstract: The electrical conductivity (EC) of minerals found on Earth and throughout the solar system is a fundamental transport property that is used to understand various dynamical phenomena in planetary interiors. High-pressure and high-temperature ( P–T) EC measurements are also an important tool for observing phase transitions. Impedance measurements can accurately measure the EC of a nonmetallic sample. In previous measurements under static conditions using a laser-heated diamond-anvil cell (LHDAC), only direct cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Okuda et al [55] tested the in situ resistivity of NaCl under the condition of an LH-DAC and found that the resistance tended to [41] Copyright 2019, APS.…”
Section: Electrical Performance Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Okuda et al [55] tested the in situ resistivity of NaCl under the condition of an LH-DAC and found that the resistance tended to [41] Copyright 2019, APS.…”
Section: Electrical Performance Measurementmentioning
confidence: 99%
“…Okuda et al [ 55 ] tested the in situ resistivity of NaCl under the condition of an LH‐DAC and found that the resistance tended to decrease with an increase in temperature at 21 and 33 GPa, as shown in Figure a and b. Hong et al [ 56 ] investigated the structural and electrical transport properties of natural barite under the conditions of 298–873 K and 1.5–35 GPa using a DAC through electrical conductivity measurements.…”
Section: In Situ Measurement Of Electrical Thermal Magnetic and Acous...mentioning
confidence: 99%
See 1 more Smart Citation
“…Here we measured the EC of molten dense MgSiO 3 , representing the chemical composition of terrestrial magma ocean, at 39–71 GPa and 3460–4490 K by a pseudo‐four‐probe direct current resistance measurement and a recently‐developed cell configuration capable of measuring the conductivity of transparent materials in a laser‐heated diamond‐anvil cell (DAC) (Okuda et al., 2022).…”
Section: Introductionmentioning
confidence: 99%